2012
DOI: 10.1002/eji.201242397
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Akt1 signals attenuate B‐cell receptor signaling and proliferation, but enhance B‐cell migration and effector function

Abstract: Ligation of the BCR induces a complex signaling network that involves activation ofAkt, a family of serine/threonine protein kinases associated with B-cell development, proliferation, and tumor formation. Here, we analyzed the effect of enhanced Akt1 signals on B-cell maturation and function. Unexpectedly, we found that peripheral B cells overexpressing Akt1 were less responsive to BCR stimuli. This correlated with a decrease in Ca 2+ -mobilization and proliferation, in an impaired activation of Erk1/2 and mam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Consistent with our observations, Pierau et al (7) demonstrated that constitutive Akt1 signals attenuate B-cell receptor signaling and proliferation, but enhance B-cell migration and effector function. Moreover, our results also demonstrated that overexpression of Akt1 promoted the cell migration and invasion of human liver cancer HepG2 cells; however, it attenuated the cell migration and invasion of human colorectal carcinoma HCT 116 cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with our observations, Pierau et al (7) demonstrated that constitutive Akt1 signals attenuate B-cell receptor signaling and proliferation, but enhance B-cell migration and effector function. Moreover, our results also demonstrated that overexpression of Akt1 promoted the cell migration and invasion of human liver cancer HepG2 cells; however, it attenuated the cell migration and invasion of human colorectal carcinoma HCT 116 cells.…”
Section: Discussionsupporting
confidence: 92%
“…However, the role of Akt1 in cell proliferation remains controversial. For instance, a recent article indicated that constitutive Akt1 signals attenuate B-cell receptor signaling and proliferation (7). Therefore, it is essential to investigate whether ectopic expression of Akt1 promotes cell proliferation or not in other cell types, including hepatocellular carcinoma (HCC) and colorectal cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Together, these findings indicate that gliomas recruit MCs by secreting MIF, which induces the migration of these cells through mechanisms involving signaling by STAT5. This conclusion is in agreement with observations that STAT5 enhances migration by other immune cells, e.g ., B‐cells (Pierau et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of AKT has been shown to promote migration of Th1 lymphocytes via CD152/CCL4/CCR5-mediated PI3K activation [10]. Further, constitutive activation of AKT during B cell maturation lead to increased STAT5 activation and cell migration to the chemokine SDF1a [11]. Furthermore, hematopoietic stem cells (HSCs) are highly sensitive to AKT/mTOR signaling and importantly; increased activation of AKT in HSCs induces AML at the expense of HSC pool [12].…”
Section: Resultsmentioning
confidence: 99%